Larvicidal Activity of Ethyl Acetate Leaf Extract of Aegle marmelos (L.) Correa Against Aedes aegypti - Monica Puspa Sari; Rina Priastini Susilowati; Kris Herawan Timotius (HAYATI Journal of Biosciences, 2023)
Aegle marmelos leaf contains secondary metabolites that have bioinsecticidal effects. This study aimed to analyze phytoconstituents of the ethyl acetate extract of Aegle marmelos leaves, its larvicidal activity, and its effects on histopathological changes of the midgut of Aedes aegypti larvae. The ethyl acetate extract was obtained from the concentrated maceration of the leaf powder and analyzed with GCMS. The instar III or IV larvae were used and divided into six groups where each group was exposed to an extract with a concentration of 1%; 4%; 8% and 16%, and one other control group without exposure to such extract. The histopathology of larval midgut was prepared, stained with Hematoxyllin-Eosin, and observed using light microscopy. GC-MS analysis revealed that the extracts contain 8 compounds, Oleic acid, 9-Hexadecenoic acid, Cis-1,3-Eicosenoic acid, Dasycarpidan-1-methanol, acetate (ester), Digitoxin, Z-(13,14-epoxy)tetradeg-11-en-ol acetate; 2,3-dimethyl-5-trifluoromethyl-1-phen-1,4-diol, ethyl iso-allocholate. Probit test revealed that the LC50 value of ethyl acetate extract of Aegle marmelos leaves was 3.917% and histopathological results are damage to brush borders, nucleus and nucleolus, epithelial cells, and hypertrophy of the gastric caeca. The leaf ethyl acetate extract from Aegle marmerlos can be considered as a probable natural insecticide to kill Aedes aegypti. Aegle marmelos can be applied as natural insecticide to eradicate the population of Ae. aegypti.